Community Integrative Ethnomedicine for Diabetes Prevention: A Holistic Community Empowerment Approach - Isnaini Chantika Yuliandari; Dhia Jinan Naura Nidaulhaq; Shabina Nurizzati; Wulan Riandini; Fatihah Halimatul Azizah; Oktavia Ramadhani Eka Fitri; Devita Fitri Azzahra; Dwi Setiani Sumardiko; Rini Hamsidi (Tarqabin Nusantara Group, 2026)
Introduction: Diabetes mellitus (DM) remains a major global public health challenge, particularly in low- and middle-income countries where delayed diagnosis and inadequate preventive behaviors contribute to increasing disease burden. This study evaluated the effectiveness of a holistic community empowerment program combining diabetes education, self-acupressure training, preventive herbal medicine education, and opportunistic blood glucose screening, while introducing an integrated conceptual direction for community-based diabetes prevention. Methods: A one-group pretest–posttest pre-experimental study, reported according to the TREND Statement, was conducted among 30 women aged 40–60 years participating in the Family Welfare Movement (PKK) Indonesia. Diabetes knowledge was assessed using the 24-item Diabetes Knowledge Questionnaire before and immediately after the intervention. Results: Twenty participants completed both knowledge assessments, while 16 underwent blood glucose screening. Participants demonstrating poor diabetes knowledge decreased from 70.0% at baseline to 0% after the intervention, whereas good knowledge increased from 0% to 100%. Blood glucose screening identified 14 participants (87.5%) within the normal range and two participants (12.5%) with random blood glucose levels exceeding 200 mg/dL, prompting immediate referral for further clinical evaluation. Conclusion: Integrating health education, self-acupressure, preventive herbal medicine, and opportunistic screening within existing community organizations is a feasible and culturally responsive strategy for strengthening diabetes prevention. These findings provide preliminary support for the proposed Community Integrative Ethnomedicine Prevention (CIEP) Model, which conceptually integrates health literacy, evidence-informed traditional medicine, community empowerment, and early metabolic surveillance as an emerging framework for sustainable diabetes prevention.